TANTANGAN GURU SD DALAM IMPLEMENTASI MEDIA DIGITAL PADA MATA PELAJARAN IPAS KELAS 4 - Nur Rahmadaniyah; Noraisyah; Angela; Ahmad Suriansyah; Wahdah Refia Rafianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The use of digital media in fourth-grade elementary school IPAS (Science and Social Studies) learning is a 21st-century educational damand aimed at increasing student engagement and developing critical thinking skills. This study aims to identify and analyze the challenges faced by elementary school teachers in implementing digital media in IPAS learning. The method employed was a literature review of five scientific articles published between 2020 and 2025. Data analysis was conducted through stages of data reduction, categorization, and thematic interpretation. The results indicate that digital media such as interactive videos, augmented reality, and digital learning platforms can enhance students’ conceptual understanding and learning outcomes. However, teachers still encounter various challenges, including limited facilities and infrastructure, low levels of teachers’ digital competence, difficulties in classroom management, and the potential for student distraction during the use of digital media. Therefore, improving teachers’ competencies, providing adequate facilities, and implementing well-planned instructional strategies are necessary to ensure that the integration of digital media in IPAS learning can be carried out effectively and optimally.